SYSTEMATIC LITERATURE REVIEW: THE INFLUENCE OF INTERPERSONAL COMMUNICATION AND SERVICE QUALITY ON CUSTOMER LOYALTY IN THE BANKING BUSINESS - Dede Sudiana; Sandy Pratama; Yanneri Elfa Kiswara Rahmantya (SEAN Institute, 2023)
This systematic literature review research explains the influence of interpersonal communication and service quality on customer loyalty in the banking business. Nowadays, humans are in an era of cutting-edge technology, the function of the banking industry to advance and maintain the economy of a country is very important. With so many banking businesses nowadays, marketing in the banking business is very important for competition in the banking business world. The services provided by customer service officers to customers are closely related to communication, especially interpersonal communication. To achieve customers who are loyal to the banking business they run, interpersonal communication is needed to learn. When someone interacts through communication with other parties and the results of self-assessment are mostly obtained from ongoing communication, especially in meetings between customer service officers and customers. After good interpersonal communication is followed by how good service quality is a competitive weapon to win customer loyalty, then service quality can also be a benchmark for how well the level of service provided is able to meet the expectations or expectations of customers in the banking business. The results of several studies say that Interpersonal communication from response, alignment, openness and trust can influence customer loyalty in the banking business, then supported by service quality from empathy, responsiveness, reliability, physical evidence and guarantees to make customers more confident and loyal to our banking business.